Investigação da atividade biológicas dos adutos de Morita-Baylis-Hillman sobre Leishmania spp - Rocha, Juliana da Câmara (2018)
Leishmaniasis treatment is based on the use of pentavalent antimonial compounds, as first choice drugs; even though they are highly toxic presenting several side effects. This diseases complex is a public health problem, with challenges in the new therapies identification that allow a greater adhesion and better quality in the treatment of the patients. Due to high toxicity and drug resistance, the search of new alternatives for the treatment of leishmaniasis is justified. In this context, this study aimed to evaluate the anti-Leishmania activity of Morita-Baylis-Hillman adducts in vitro and ex vivo experimental models. Activity of the compounds on the promastigote and axenic amastigote forms of the Leishmania parasite, in addition to the human peripheral blood monuclear cells, were evaluated by the MTT colorimetric test (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium). The rate of infection in human monocytes and the cell death profile of promastigote forms were assessed by flow cytometry. In addition, hemolytic activity on human erythrocytes and indirect evaluation of nitric oxide levels by Griess's reagent were measured. Screening of 36 molecules from the Morita-Baylis-Hillman reaction on L. donovani's promastigote forms had MBH-A12 and MBH-A13 as one of the lowest IC50 values (4.71 and 0.37 μg/mL), besides they present the same chemical synthesis process, being thus selected for the continuation of the biological evaluation. These two substances also showed significant inhibition of growth (IC50) on the promastigote forms of L. infantum (5.6 and 5.3 μg/mL), L. amazonensis (13.2 and 13.4 μg/mL) and L. braziliensis (16.32 and 19.09 μg/mL). In addition, they showed activity on the axenic amastigote forms of L. infantum (EC50 of 9.08 and 10.76 μg/mL) and L. amazonensis (EC50 of 13.4 and 10.4 μg/mL), demonstrating effect on the diversity of Leishmania species that cause different clinical manifestations. Among the tested concentrations, these drugs did not present toxicity to peripheral blood mononuclear cells and human erythrocytes, thus demonstrating selectivity indices to parasite tropism. In the infection model evaluation of human monocytes, we did not observe statistical difference with the substances treatment, nor in modulation via nitric oxide synthesis. Cell death profile in Leishmania spp. suggests a pattern involving apoptosis death mechanism for MBH-A12 and MBH-A13 adducts, different from amphotericin B which also leads to the necrosis process. Thus, we concluded that the Morita-BaylisHillman adducts are compounds with expressive anti-Leishmania activity in an in vitro model, being molecules that need to be better investigated, regarding to the action mechanism, in the search for new treatments for leishmaniasis.